Chronic bronchitis, work related respiratory symptoms, and pulmonary function in welders in New Zealand. Issue 3 (March 1998) - Bradshaw, L M; Fishwick, D; Slater, T; Pearce, N
Abstract : OBJECTIVES: A cross sectional study of respiratory symptoms and lung function in welders was performed at eight New Zealand welding sites: 62 current welders and 75 non-welders participated. METHODS: A questionnaire was administered to record demographic data, smoking habit, and current respiratory symptoms. Current and previous welding exposures were recorded to calculate a total lifetime welding fume exposure index. Forced expiratory volume in one second (FEV1), forced vital capacity (FVC), and peak expiratory flow (PEF) were measured before the start of the shift. RESULTS: There were no significant differences in ethnicity, smoking habits, or years of work experience between welders and non-welders. Symptoms of chronic bronchitis were more common in current welders (11.3%) than in non-welders (5.0%). Of those workers with a cumulative exposure index to welding fume > or = 10 years, 16.7% reported symptoms of chronic bronchitis compared with 4.7% of those with a cumulative exposure index < 4 years (odds ratio (OR) 4.1, 95% confidence interval (95% CI) 0.90 to 17.6). Workers with chronic bronchitis had significantly lower measures of baseline PEF (p = 0.008) and FEV/FVC ratio (p = 0.001) than workers without chronic bronchitis. Multivariate analysis showed that current smoking (OR 9.3, 1.0 to 86.9) and total exposure index to welding fumes > 10 years (OR 9.5, 1.3 to 71.9) were independent risk factors for chronic bronchitis. The report of any work related respiratory symptom was more prevalent in welders (30.7%) than non-welders (15.0%) and workers with these symptoms had significantly lower FEV, (p = 0.004) and FVC (p = 0.04) values. Multivariate analysis identified a high proportion of time spent welding in confined spaces as the main risk factor for reporting these symptoms (OR 2.8, 1.0 to 8.3). CONCLUSION: This study has documented a high prevalence of symptoms of chronic bronchitis and other work related respiratory symptoms in current welders. Also, workers with chronic bronchitis had reduced PEF and FEV/FVC compared with those without chronic bronchitis. These symptoms related both to cigarette smoking and a measure of lifetime exposure to welding fume.